Effectiveness and Efficiency of the State Revenue and Expenditure Budget Policy in South Sumatra: Islamic Perspective Study - Setyadi, Bakti; Helmi, Sulaiman; Mohamad, Syed Ismail Syed (IKONOMIKA, 2023)
Effective and efficient management of state finances has an essential role in Islam. This exploratory, descriptive study aims to analyze the effectiveness and efficiency of state revenue and expenditure budget policies in South Sumatra from an Islamic perspective. This research was conducted at the South Sumatra Provincial Government, especially at the South Sumatra Provincial Archives Service. Data were obtained from interviews, observations, and secondary sources, such as regional financial reports and South Sumatra audit reports, published publicly. Analysis of data on the ratio of effectiveness and efficiency is calculated by comparing the realization of APBD revenues with revenue targets. The results of the study show that the implementation of state revenue and expenditure budget policies in South Sumatra has been effective and efficient. In addition, the realization of the budget is also the same between the expected targets and the results obtained in the implementation of the state revenue and expenditure budget policy in South Sumatra. The principles of Islamic economics in the context of state financial management are based on fairness, justice and social welfare, and emphasize the importance of ethical behavior and transparency in economic transactions. It is very important to ensure that the government's revenue and expenditure policies are in line with the general objective of increasing social welfare and ensuring economic equity. The findings of this study indicate that the Provincial Government of South Sumatra has effectively implemented revenue and expenditure policies that are in line with sharia economic principles.